Analisis Yuridis Perlindungan Hukum Anak Hasil Perkawinan Tidak Dicatatkan di Pemerintahan: Kajian Kritis dari Perspektif Undang-Undang No. 1 Tahun 1974 Tentang Perkawinan - Ifham, Dhiyaul Habib; Hasibuan, Pagar; Matsum, Hasan; Lubis, Fauziah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
Unregistered marriages remain a common phenomenon in Indonesian society and raise various legal issues, particularly regarding the status and protection of children born from such marriages. This study aims to analyze the regulation of unregistered marriages according to Law Number 1 of 1974 concerning Marriage, examine the resulting legal consequences, and examine the forms of legal protection for children resulting from unregistered marriages. This study uses a normative legal research method with a statutory, conceptual, and case approach, primarily through an analysis of statutory regulations, legal doctrine, and Constitutional Court Decision Number 46/PUU-VIII/2010. The results of the study indicate that although unregistered marriages can be considered valid according to religion, they do not have formal legal force in the eyes of the state, resulting in the failure to fulfill children's civil rights, such as the right to maintenance, inheritance, and legal identity. The Constitutional Court decision has expanded the recognition of civil relations between children and their biological fathers, but its implementation still faces legal and social obstacles. Therefore, it is necessary to strengthen regulations, increase public legal awareness, and reform marriage registration policies to ensure fair and comprehensive legal protection for children as subjects of human rights.